TEACHER-CHILD INTERACTIONS IN LEARNING ACTIVITIES - Nordin Mamat, Loy Chee Luen, Nor Mashitah Mohd Radzi ,Nurul Hasyimah Mat Rani, Mazlina Che Mustafa ,Syahida Iryani Mohd Yusoff ,Mohd Mahzan Awang (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
This study aims to identify Teacher-Child verbal and non-verbal interactions in learning activities at early childhood education centres. Verbal interaction encompasses praise, persuasion, instruction, prompting, pampering and advice. Non-verbal interaction encompasses language, touching and facial expression. This study use qualitative data. A total of 10 teachers in Kedah, Malaysia were selected to complete a checklist related to verbal and non-verbal interaction during learning activities. The findings show that, for verbal interactions, nine of teachers are not pampering children. All teachers give praise and advice and nine of teachers use persuasion, instruction and prompting on children during learning activities. In non-verbal interactions, all teachers use sign language, nine teachers use facial expressions and eight employ touch gestures with children. In conclusion, verbal and non-verbal interactions play important roles in learning activities and assist the development of children, especially in terms of language and social skills.